Transition between high‐spin and low‐spin states in Mn‐doped MgO. Issue 4 (14th February 2014) - Meskine, S.; Boukortt, A.; Hayn, R.; Zaoui, A.
<x xml:space="preserve">Abstract</x> Using first‐principle band structure methods, we investigate the electronic and magnetic properties of Mn‐doped MgO in rock salt structure. Two approaches have been compared: the local spin‐density approximation (LSDA) and the LSDA + U with a Hubbard‐like Coulomb term. In both approximations, by reducing the lattice parameter, a transition from the high‐spin (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9j9rg0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />S=5/2</alternatives>) to a low‐spin (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9j9p96" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />S=1/2</alternatives>) state has been found. The high‐spin state is insulating, whereas the low‐spin state corresponds to a half‐metallic ferromagnet if the Jahn–Teller effect can be avoided.